Comparative Efficacy and Safety of Diacerein in Patients with Knee Osteoarthritis: A Pilot Study - Shakya Shrestha, S.; Tamrakar, S.; Shrestha, R.; Shrestha, R.; Basi, A.; Malla, M.; Khadka, S. K. (Kathmandu University Medical Journal, 2021)
Background Osteoarthritis (OA) is the most common chronic rheumatic disease. The prevalence of OA is skyrocketing with time. Providing a proper treatment regimen for OA is also growing as a major public health challenge. Conventional pharmacological treatments are mainly for alleviating pain and have some severe adverse effects. Diacerein is a new oral anti-inflammatory drug especially developed for the management of OA having only mild to moderate adverse effects. However, the evidence of efficacy and safety of Diacerein in OA is not well documented and yet to be explored. Objective To compare the efficacy and safety of Diacerein in knee OA with conventional nonsteroidal anti-inflammatory drugs (NSAIDs). Method A comparative study was conducted among knee OA patients attending Out- Patient Orthopedic department in Dhulikhel Hospital, Nepal from December 2019 to September 2020, using self-structured and standard questionnaire. The patients were randomized to receive either a conventional standard treatment (Treatment Group I: NSAIDs) or alternative treatment regimen (Treatment Group II: NSAIDS+ Diacerein). Patients were followed-up after two months and data were analyzed using SPSS 21.0. Result Among 72 patients enrolled in this study, majority (44.44%) were between 51-60 years of age in which 81.94% of the patients were female. Post treatment data was collected from 15 participants. The mean KOOS-PS score of the participants in Treatment Group I decreased from 35.56 ± 14.33 to 35.14 ± 12.65 while that of the Treatment Group II participants reduced from 63.31 ± 12.08 to 49.99 ± 13.10 in two months. Similarly, the mean WOMAC score decreased from 46.87 ± 17.80 to 34.37 ± 16.83 in Treatment Group I and from 54.23 ± 14.66 to 46.22 ± 12.16 in Treatment Group II. The mean Lysholm score in Treatment Group I increased from 55.57 ± 8.16 to 60.86 ± 15.01 and in Treatment Group II, it increased from 46.62 ± 13.01 to 60.25 ± 17.598. Conclusion Diacerein treatment group had better functional outcome compared to the patients in the treatment group with conventionally used drugs. Also, the adverse effects faced by the patients were minor. The current study are suggestive of better efficacy and safety of Diacerein compared to other drugs.